The efficient and fair approval of multiple-cost - single-benefit projects under unilateral information - Nava Kahana; Yosef Mealem; Shmuel Nitzan (Institute for the Study of Labor (IZA), 2009)
This paper focuses on indivisible multiple-costsingle-benefit projects that must be approved by the government. A simple mechanism is proposed that ensures an efficient and fair implementation of such projects. The proposed mechanism is appropriate for a unilateral information structure: the single beneficiary has complete information on the cost and benefit of the project while the government official has no such information and the cost bearers have information only on each other's costs.
urn:nbn:de:101:1-2009061254
Keywords: D61; D62; D78; 330; Indivisible project; single beneficiary; multiple-cost bearers; unilateral information; efficient and fair implementation; Genehmigung; Investition; Projektbewertung; Asymmetrische Information; Mechanism Design; Theorie